Evaluation of aroma release of gummy candies added with strawberry flavours by gas-chromatography/mass-spectrometry and gas sensors arrays. (December 2015) - Pizzoni, D.; Compagnone, D.; Di Natale, C.; D'Alessandro, N.; Pittia, P.
Highlights: The aroma release of flavouring agents of different origin from food matrices needs to be studied. Gummy candies made of different structuring were added with natural or nature-identical aroma. Differences in aroma release of the differently formulated candies resulted by GC–MS analysis. E-nose with two set of sensors discriminated samples by structuring agent and aroma origin. Sensory analysis showed results different from those obtained from instrumental analysis. Abstract: Aroma release of two strawberry flavourings (one natural-NS and one nature-identical-NIS) at different concentration (0.15%, 0.30%) added to gummy candies made of pectin, gum arabic and gelatine as structuring agents was studied by gas chromatography/mass-spectrometry (GC–MS) and electronic nose (e-nose) equipped with two different sets of sensors to characterise and differentiate the products. By using GC–MS, different aroma patterns of the pure NS and NIS flavouring were obtained. The effect on the presence and amount of the volatile compounds of the strawberry flavours in the vapour phase was studied and discussed as a function of the candies formulation; the products were partly differentiated, in agreement also with the sensory analysis. The innovative e-nose instrument has differentiated candies based on flavour origin and concentration for both gelatine and gum arabic independently on the sensor array type; for the pectin-based products porphyrines and GNP showed lower and different performances in the discrimination ability.